STRUCTURE FUNCTIONAL DESCRIPTION OF LYMPH NODES OF MUCOSA OF STOMACH’S FUNDAL DEPARTMENT AT ACUTE EXPERIMENTAL GASTRITIS AND INTRODUTION OF PREPARATION "PLATEX - PLACENTAL" - Bilash, S.M. (World of Medicine and Biology, 2012)
The mechanisms of immunoreactions and quantitative changes of immunocompetency cells which take place in the lymph nodes of mucosa of stomach’s fundal department at acute experimental gastritis are in-process studied, introdution of preparation "Platex - placental" and introdution preparation "Platex - placental" on a background acute experimental gastritis. It is set, that immunity reactions passed on a humoral type. At influence of preparation "Platex - placental" on a background acute experimental gastritis they flowed quicker and more tolerant.
Keywords: stomach; acute experimental gastritis; preparation "Platex - placental"; lymph node; immunocompetency cells